Cálculo de Requisitos de Capacidade para a Técnica Patching de Compartilhamento de Recursos - Souza e Silva, Edmundo; Leão, Rosa M. M.; Diniz, Morganna C. (Journal of Communication and Information Systems, 2017)
In the past few years several bandwidth sharing techniques for multimedia servers have been proposed in the literature in order to improve their scalability. One of these techniques is patching. The main advantages of patching are: (i) the simplicity of implementation and (ii) efficiency. In other words, conside1ing a video with popularity varying from low to medium, the patching scheme requires, in the average, the same transmission bandwidth as other more sophisticated techniques. Recently, a simple expression to estimate the average bandwidth required by the patching technique has been obtained in the literature. However, averages values do not always provide an accurate estimation of the requirement bandwidth. We propose an analytical model to compute the distribution of the bandwidth required by the patching technique. We investigate the behavior of the disttibution when we vary the size of the patching window. We also analyze the QoS obtained when the averaae bandwidth is used to dimension the server.